Siberian larch forests and the ion content of thaw lakes form a geochemically functional entity - Herzschuh, Ulrike (Prof. Dr.); Pestryakova, Luidmila A. (Prof. Dr.); Savelieva, Larissa A.; Heinecke, Liv (Dr.); Böhmer, Thomas; Biskaborn, Boris (Prof.); Andreev, Andrei; Ramisch, Arne (Dr.); Shinneman, Avery L. C.; Birks, H. John B. (Nature Communications, 2013)
Siberian larch forests growing on shallow permafrost soils have not, until now, been considered to be controlling the abiotic and biotic characteristics of the vast number of thaw-lake ecosystems. Here we show, using four independent data sets (a modern data set from 201 lakes from the tundra to taiga, and three lake-core records), that lake-water geochemistry in Yakutia is highly correlated with vegetation. Alkalinity increases with catchment forest density. We postulate that in this arid area, higher evapotranspiration in larch forests compared with that in the tundra vegetation leads to local salt accumulation in soils. Solutes are transported to nearby thaw lakes during rain events and snow melt, but are not fully transported into rivers, because there is no continuous groundwater flow within permafrost soils. This implies that potentially large shifts in the chemical characteristics of aquatic ecosystems to known warming are absent because of the slow response of catchment forests to climate change.